QUARTER LIFE CRISIS DALAM MEMBANGUN KONSEP DIRI: Studi Fenomenologi Pada Fresh Graduate - Hanifa Audelia, (2023)
The phenomenon of quarter life crisis symptoms or anxiety symptoms is usually felt by individuals aged around 20, where feelings of anxiety or worry arise, which are caused by uncertainty about future life, whether career or work issues, education, social relationships, or life partner. This research aims to find out and understand how fresh graduates interpret the quarter life crisis in building self-concept, as well as knowing the factors that have an impact on building self-concept in fresh graduates when experiencing a quarter life crisis. The theory used in this research is Edmund Husserl's phenomenological theory, which holds that a reality or experience provides awareness of something, the individual is the main actor in determining the meaning of his experience. Researchers used qualitative research methods with a phenomenological approach. Phenomenology is the right approach to study more deeply a person's experience of a phenomenon. Researchers conducted in-depth interviews with 6 fresh graduates aged 21-25 years and one clinical psychologist to validate the data, using a purposive sampling technique, namely determining informants based on specified criteria. The results of the research obtained the meaning of the presence of quarter life crisis symptoms in individual perceptions. There are internal and external factors that have an impact on developing an informant's self-concept when experiencing symptoms of a quarter life crisis. These internal factors consist of self-actualization and experience, and external factors consist of a reference group which includes family, friends, and lecturers or instructors.